Comparative Effects of Strain Counterstrain and Ischemic Compression Technique in Patients with Upper Trapezius Trigger Points - Samra Saleem, Sehar Zahid Chaudhry, Muhammad Usama Sohail, Ramish Saleem, Hira Rafique, Farwa Batool, Atif Ali Attar, Sana Shah (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The trigger points are hyperirritable spots found usually in the muscle fascia or within the taut bands of skeletal muscles that is painful on compression. Ischemic compression technique uses the application of sustained pressure with sufficient force and for long enough so as to slow down the flow of blood and releasing tension out of the muscle. Strain counterstrain (SCS), also known as positional release, is a passive positional treatment that relieves musculoskeletal pain and dysfunction by indirect hand manipulation. Objectives: The aim of this study was to compare the effects of ischemic compression technique and strain counterstrain technique on pain, neck lateral flexion and disability in patients with upper trapezius trigger points. Methodology: The RCT was conducted on 36 male and female participants aging 25-45 having maximum of 5 trigger points in the upper trapezius bilaterally. The patients were divided equally to ischemic compression and strain counterstrain group by lottery method. The treatment was given for 3 days a week for 4 weeks. The NPRS, NDI and cervical lateral flexion were used as outcome measure. The assessment of the outcome measures was done on baseline, after 2nd week and after 4th week. The data was analyzed by SPSS version 26 using appropriate tests depending upon the normality by keeping the level of significance at 0.05. Results: Out of 36 participants (Mean age 32.96 ± 5.91), 20 were male and 16 were female, 3 participants lost to follow up. The within group analysis of NPRS and NDI done by Friedman test and that of cervical flexion done by repeated measures ANOVA showed that the both the interventions has produced significant (p<0.05) effects on pain, neck disability and range of motion, but the between group analysis of NPRS and NDI done by Mann-Whitney test and that of Cervical ROM done by Independent samples t-test showed that none of the two technique produced significant results (p>0.05) as compared to the other in subjects with upper trapezius trigger points. Conclusion: A 4-week intervention of the ischemic compression and strain counterstrain produced significant results in reducing the intensity of pain, the cervical disability and improving the cervical range of motion, but the intergroup comparison showed that both the ischemic compression and strain counterstrain were equally effective and none of them produced significant results as compared to others on patients with upper trapezius trigger points. Keywords: Ischemic Compression Technique; Strain Counterstrain; Upper Trapezius Trigger Points.